Pertumbuhan Dan Hasil Bawang Merah (Allium ascalonicum L.) Pada Beberapa Jenis Dan Dosis Bahan Organik - Buhaira Buhaira; Delma Sonia; Made Deviani Duaja (Universitas Batanghari, 2022)
This research aimed is to get one kind of best organic material on onion bulb production (Allium ascalonium L.). This experiments using Randomized Block Design of one factor combinations of species and dosage of organic matter. Organic materials used are compost of chicken coop, cow shed, goat cage, solidand municipal waste with dose of 10 ton ha-1 and 15 tons ha-1. Parameters observed were plant height, number of leaf, number of tillers, fresh tuber weight per hill and tuber weight per plot. Provision of several types and doses of organic matter had no significant effect on plant height, number of leaves, number of tillers, but significantly affected tuber weight per clumpand productivity (tuber weight per hectare). Dosage and type of organic material that gives the best onion bulb weight is compost chicken coop 15 ton ha-1